ANALISIS KAITAN PENDIRIAN TERHADAP RESILIENSI SISWA SMA AL-ULUM MEDAN YANG ORANG TUANYA BERCERAI - Dian Reka; Dwi Indah Yulianti; Zefrullahranasagala; Annisa Misyazara Naryani; Nurasakinah Daulay (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose of this study was to find out whether there is a relationship between Establishment and resilience in Al-Ulum Medan Private High School students whose parents divorced. The hypothesis of this study is that there is a relationship between self-esteem and resilience in adolescents whose parents are divorced. The population of this study consists of teenagers whose parents are divorced in Indonesia. 100 people were sampled for data collection. Data collection technique using purposive sampling. The measurement tools are flexibility which refers to aspects of Reivich and Shatte (2002), and self-esteem which refers to aspects of Coopersmith (1967). Data analysis was performed using the Pearson product-moment correlation technique. The results of the correlation analysis showed a significance value of 0.000 (p <0.05) and a value of r = 0.836 which means that there is a significant positive relationship between self-esteem and resilience.